A study of the GB rail socio-technical system: developing guidance for implementing sustained improvements in safety and performance - Nolan-McSweeney, Michelle (2023)
The rail industry in Great Britain has faced unprecedented demand for its services in the past decade, whilst addressing technological transformation, and with multiple objectives in relation to safety and performance. Sociotechnical systems theory seems to offer solutions for these challenges, but there has been little research on how rail organisations can establish processes and build resilience during periods of significant change that are complementary with this type of theoretical approach. This thesis describes the studies undertaken between late 2014 and December 2020 to evaluate the GB rail socio-technical system and reflects on the impact of change on frontline staff, going on to describe organisational learning and the systems approach to safety-driven design. Two national change programmes (Business Critical Rules (BCR), and Planning and Delivering Safe Work (PDSW)) affecting the frontline rail engineering workforce have been used as contexts to frame consultations within this study. Five studies were conducted and are described in Chapters 5 to 9. A total of twenty-eight interviews were undertaken as part of Studies 1 and 2 (Chapters 5 and 6), with senior executives and managers in the railway industry, to investigate how they, as senior business leaders, describe the management of change in a complex rail socio-technical system. These interviews were designed to explore the perceptions of industry personnel in policy setting and senior management roles and what they see as barriers to change within a dynamic, fast moving, industry. This included exploring both the ‘work as imagined’ in the corporate strategy and company procedures, as well as their understanding of ‘work as done’, including some interviews specifically addressing the roll out of the two national change programmes. An employee survey, using a questionnaire, was sent out to a select group of frontline staff as part of Study 3 (Chapter 7). There were 1355 responses to this survey, helping to understand the perceptions of the changes at the ‘sharp end’. A longitudinal (observational) study was also undertaken (over 6 years), and this Study 5 (Chapter 9) tracked the change programmes as they progressed and the effects of changes as they have occurred, including delivery of safety and performance targets during the coronavirus pandemic. In order to provide recommendations to aid the industry in forward planning, Study 4 (Chapter 8) considered two different techniques / analysis methods, and whether they are suitable for prospective analysis. Both STAMP (the Systems Theoretic Accident Modelling and Process model) and the bow-tie analysis technique (used by Network Rail) were evaluated to determine their suitability as prospective tools for industry to use to support future interventions in change programmes. The results of the five studies, when combined, identify what should be considered when designing change in a complex industry, and how a socio-technical system framework or model might go on to be applied in practice, whilst calling for greater user-centred input. It is also clear from the research, particularly Study 2 (Chapter 6), that a systemic approach is required, considering social and technical aspects concurrently, as change programmes are implemented (among other workstreams and competing priorities). The thesis outputs are recommendations that help guide the implementation of sustained improvements in safety and performance in GB rail and culminate in a series of steps guiding managers and programme teams on how they might design, implement, and embed change. The thesis concludes by reflecting on the contribution that this work makes to the bodies of knowledge in socio-technical system theory, resilience engineering, and human factors / ergonomics (HFE).